Keaktifan Belajar Siswa SD pada Pembelajaran IPA Menggunakan Model Pembelajaran Make A Match - Anisah, Siti; Erviana, Lina; Purnamasari, Mega Isvandiana (Scholarly Journal of Elementary School, 2023)
The purpose of this study was to find out (1) the use of the Make A Match learning model in fifth grade science learning at SDN 2 Gunungsari. (2) the activeness of student learning after using the Make A Match learning model in class V Science learning at SDN 2 Gunungsari. (3) the supporting and inhibiting factors of student activity in learning science using the Make A Match learning model for class V SDN 2 Gunungsari. This research uses a qualitative descriptive research type. Data collection techniques with observation techniques, interviews, questionnaires and documentation. Data analysis techniques using data reduction techniques, data presentation, and drawing conclusions. The results of data analysis obtained 1. Learning using the Make A Match learning model with paired card media is able to attract attention, students' enthusiasm so that learning does not feel bored and bored. 2. Students actively participate in science learning using the Make A Match learning model. Can make students more active in asking, arguing, discussing exchanging information and being able to solve problems given by the teacher. 3. Factors supporting learning using the Make A Match learning model, namely learning and directed material, not rigid, student interaction, responsibility, and student knowledge. learning inhibiting factors using the Make A Match learning model, namely student disorder.